Post-operative complications of displaced unstable distal end radius fracture treated by volar plating - Ambulgekar, Rajesh K.; Gurnani, Vishal (International Journal of Research in Orthopaedics, 2020)
Background: Fracture of the distal radius (DRF) is one of the most common fractures present in emergency. The most common operative treatments of these fractures are open reduction and internal fixation with volar locking plates. The incidents and types of complications associated with the use of these operations is an ongoing process till date. The objective of the study was to find demographic profile of patients of displaced unstable distal end radius fracture, and to study the post-operative complications among above patients treated by volar plating. Methods: We performed a prospective study documenting types of complications and their occurrence in a group of patients who received open reduction and internal fixation. Our definition of a complication was a case in which the patient had one or more complications which required an intervention medical or surgical. Results: A total of 33 patients were included, most of the cases, (63.63%) were from the age group 21-40 years. We had 4 cases (12. 12%) females, and 29 cases (87.88%) males. Post-operative complications were noted in 7 individuals 22.2 % and no complications noted in 26 cases (78.8%). In 30 cases there was no any deformity found in postoperative one year follow up, 2 patients develop prominent ulnar styloid found in follow up of one year ,and 1 residual dorsal tilt found after one year. Conclusions: Our finding that 22.2% suffer from complication when treated using a volar locking plate must be taken into consideration when surgeons choose between conservative or operative treatment for DRF treatment. A few other studies have looked at the incidents of complications and have reported similar results.